2014
DOI: 10.1002/stem.1758
|View full text |Cite
|
Sign up to set email alerts
|

sdf1 Expression Reveals a Source of Perivascular-Derived Mesenchymal Stem Cells in Zebrafish

Abstract: There is accumulating evidence that mesenchymal stem cells (MSC) have their origin as perivascular cells (PVC) in vivo, but precisely identifying them has been a challenge, as they have no single definitive marker and are rare. We have developed a fluorescent transgenic vertebrate model in which PVC can be visualized in vivo based upon sdf1 expression in the zebrafish. Prospective isolation and culture of sdf1DsRed PVC demonstrated properties consistent with MSC including prototypical cell surface marker expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Subsequent comparison of sdf1 DsRed tagged cells with human MSCs revealed that the zebrafish PVCs shared cell surface markers typical of MSCs, trilineage mesodermal differentiation and the capacity to support HSCs expansion in vitro. Consistent with these observations, global proteomic studies performed by tandem mass spectrometry and two‐dimensional liquid chromatography demonstrated high similarity between PVCs and human MSCs (Lund et al, ).…”
Section: Characterization Of Mscsmentioning
confidence: 69%
See 1 more Smart Citation
“…Subsequent comparison of sdf1 DsRed tagged cells with human MSCs revealed that the zebrafish PVCs shared cell surface markers typical of MSCs, trilineage mesodermal differentiation and the capacity to support HSCs expansion in vitro. Consistent with these observations, global proteomic studies performed by tandem mass spectrometry and two‐dimensional liquid chromatography demonstrated high similarity between PVCs and human MSCs (Lund et al, ).…”
Section: Characterization Of Mscsmentioning
confidence: 69%
“…The findings of Crisan et al was further confirmed in recent studies by Lund et al (2014) who utilized zebrafish engineered to exhibit red fluorescent upon expression of stromal cell-derived factor-1 (SDF-1, i.e., sdf1 DsRed ). The marker SDF-1, originally observed to be expressed in cultured bone marrow stromal cells, is known to be expressed by MSCs (Tashiro et al, 1993).…”
Section: Characterization Of Mscsmentioning
confidence: 70%
“…Other groups created zebrafish hematopoietic supportive mesenchymal stem cell lines from sdf1 :DsRed transgenic animals 54 , allowing investigation of the hematopoietic niche, positing the zebrafish as a useful model system to study niche/HSPC interactions. Importantly, ZEST cells are easily transfected, and with the advent of CRISPR/Cas9 technology, it should be possible to quickly and effectively modulate putatively important stromal factors involved in hematopoiesis in this in vitro system.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the specific cell types listed above appear to retain mesenchymal multipotency into adulthood in multiple species, further confounding terminology. It is therefore essential to define the cell type under study with both molecular markers and in vivo position in tissue relative to vascular endothelium and, optimally, its basal lamina [6]; short of these conditions, it is important to keep in mind that all markers used to date are typical of, but never restricted to, a given pericytic population [7,8]. For example, the large transmembrane glycoprotein encoded by the CSPG4 (chondroitin sulfate proteoglycan 4) gene, also known as NG2 (for nerve/glia antigen 2), is expressed by many multipotent cell types, such as mesenchymal, keratinocyte and radial glia stem cells, in addition to pericytes.…”
Section: Brief History Of the Mysterious Pericytementioning
confidence: 99%
“…Rinse abundantly in 70% ethanol (EtOH) (see Note 14). 7. Dehydrate in 90% then at least two changes of anhydrous 100% EtOH.…”
Section: Harvesting Fixation and Processing For Embeddingmentioning
confidence: 99%